Effect of thermal annealing on the structural and the optical properties of ZnO/MgO nanostructures - Panin, GN; Baranov, AN; Oh, YJ; Kang, TW; Kim, TW (ELSEVIER, 2005)
The effect of thermal annealing on the structural and optical properties of ZnO/MgO nanoparticle structures prepared by solution techniques were investigated with scanning electron microscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and cathodoluminescence (CL) measurements. The TEM examination showed that the ZnO/MgO nanoparticles annealed at 400, 600, 800, and 1000 degrees C had a crystalline wurtzite structure. The size of the particles was in the range between 10 and 100 nm. The blue shift of the CL emission of the samples after annealing at temperatures higher than 600 degrees C originated from an increase in the MnxZn1-xO band gap and the quantum confinement effect resulting from the small size of the particles. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: STIMULATED-EMISSION; BAND-GAP; ZNO; MGXZN1-XO